Yo-kai watch. 2, Beware the bristly germs - Konishi, Noriyuki; Sitterson, Aubrey (VIZ Media, LLC, 2015)
Elementary student Nate Adams sees Yo-kai all around him thanks to his Yo-kai watch. Soon he and Whisper, the ghost butler, become involved in all kinds of ghostly adventures in which Nate gets sick, meets a jibakurei ghost, and becomes a rebellious bad boy.